ADAPTASI PERUBAHAN IKLIM DAN KETERKAITANNYA DENGAN PRODUKTIVITAS DAN KETAHANAN PANGAN RUMAH TANGGA PETANI PADI DI KABUPATEN TANGGAMUS - , KTUT MURNIATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimes to (1) find out the preception and adaptation strategies of organic and non-organic rice farmers to climate change, (2) measure livelihood vulnerability of household of organic and non-organic farmers to climate change, (3) measure the effect of adaptation strategies to climate change in technical efficiency of organic and non-organic rice, and (4) measure the effect of adaptation strategies to climate change in food security of organic and non-organic rice farmersâ households. The research was carried out in Pekon Tampang Tua and Pekon Tampang Muda, Pematang Sawa Subdistrict, Tanggamus Regency. Samples were taken by census sampling of 140 respondents consisting of 60 organic rice farmers and 80 non-organic rice farmers. The analysis was using descriptive analytic method, Livelihood Vulnerability Index (LVI), Stochastic Production Frontier (SPF)and Ordinal Logit Model (OLOGOSTIC). Research result showed that: (1) The organic rice farmers and non-organic rice farmers. perceive climate change in accordance with the farmers conditions experienced, but had been reflect climate change